Revealing The Impact of ERM and ESG Disclosures on The Performance of Non-Financial Public Companies in Indonesia: An Empirical Study From 2017-2022 - Wakhid Junaidi; Dewi Hanggraeni (Green Publisher Indonesia, 2024)
This study investigates the impact of Enterprise Risk Management (ERM) disclosure on working capital efficiency, profitability, and firm value of non-financial public companies in Indonesia during the period 2017-2022. Additionally, it examines the moderating role of Environmental, Social, and Governance (ESG) disclosure on the relationship between ERM disclosure and these three variables. The research adopts a quantitative approach, utilizing secondary data from companies' annual reports. Working Capital Turnover (WCT) measures efficiency, profitability is assessed by Return on Assets (ROA), and firm value is evaluated using Tobin’s Q ratio. ERM and ESG disclosures are assessed based on the COSO ERM 2017 framework and GRI Standards, respectively. The findings reveal that ERM disclosure has a significant positive impact on firm value but shows no significant effect on working capital efficiency and profitability. Furthermore, ESG disclosure positively moderates the relationship between ERM disclosure and firm value, highlighting the synergistic benefits of integrating robust ERM practices with comprehensive ESG disclosures. This study underscores the necessity for companies to enhance the quality of their risk management and ESG-related disclosures to improve financial performance and corporate value. By providing empirical evidence on the benefits of ERM and ESG disclosures, this research contributes to the literature and offers practical implications for non-financial public companies in Indonesia.